Autobiographical memory and hierarchical search strategies in depressed and non-depressed participants - Haque, S.; Juliana, E.; Khan, R.; Hasking, Penelope (BioMed Central Ltd., 2014)
Background: There is a growing body of literature showing individuals with depression and other trauma-related disorders (e.g., posttraumatic stress disorder) recall more overgeneral and less specific autobiographical memories compared to normal participants. Although the mechanisms underlying overgeneral memory are quite clear, the search strategy operated within the autobiographical knowledge base, at time of recollection, requires further exploration. The current study aimed to examine the hierarchical search sequence used to recall autobiographical memories in depressed and non-depressed participants, with a view to determining whether depressed participants exhibited truncated search strategies. Methods: Thirteen depressed and an equal number of non-depressed participants retrieved 15 memories each, in response to 15 commonly used cue words. Participants reported the first memory that entered in their mind. All memory descriptions were recorded and later transcribed verbatim for content analysis.Results: Depressed participants retrieved autobiographical memories faster, produced shorter memory descriptions and were less likely to recall positive memories than non-depressed participants. Non-depressed participants were more likely to commence retrieval by accessing lifetime period knowledge followed by general event and event specific knowledge, whereas depressed participants showed a tendency to terminate retrieval at the general event level. Conclusions: It is concluded that depressed participants do adhere to the same hierarchical search strategy as non-depressed participants when retrieving specific autobiographical memories, but that they terminate their search early, resulting in overgeneral memories.